2019
DOI: 10.1080/10852352.2019.1603676
|View full text |Cite
|
Sign up to set email alerts
|

Social identity and drinking: Dissecting social networks and implications for novel interventions

Abstract: Drinking among young adults has been consistently associated with perceptions of prevalence and approval of varying levels of drinking among broadly defined similar others (e.g., other female college students). Less work has considered influences in terms of actual group members comprising individuals' social networks. We proposed two overlapping groups would differentially influence drinking and related consequences (important others; drinking buddies; and members of both groups). Furthermore, we expected tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…After achieving high status, which has resulted in frequent invitations to parties, students then may pose an even higher risk of excessive alcohol and drug use. In line with previous studies, results show that individuals with larger social networks, which has shown to be an indicator for social status among young, also drink more [ 35 , 61 ]. However, status can also act as a protective factor.…”
Section: Discussionsupporting
confidence: 92%
“…After achieving high status, which has resulted in frequent invitations to parties, students then may pose an even higher risk of excessive alcohol and drug use. In line with previous studies, results show that individuals with larger social networks, which has shown to be an indicator for social status among young, also drink more [ 35 , 61 ]. However, status can also act as a protective factor.…”
Section: Discussionsupporting
confidence: 92%
“…In line with earlier studies, the influence of peers and the system of norms that young people themselves create in this specific context constitute important parts in explaining the high level of alcohol consumption (32,47,48). The findings show that there are clear local drinking norms in Villaholm.…”
Section: Identity Construction In Relation To Bourdieu's Social Cultu...supporting
confidence: 80%
“…In line with Bourdieu's framework the analysis shows that by establishing relationships-via alcohol-one's social capital increases, which in turn can be exchanged for larger networks, social belonging and popularity. Previous studies show that this, in turn, increases the odds of being invited to more parties and drinking more alcohol (16,47). Alcohol consumption thus promotes young people's identity construction and social capital.…”
Section: Identity Construction In Relation To Bourdieu's Social Cultu...mentioning
confidence: 94%
“…One’s “drinking buddies,” defined as individuals from their network designated as companions for the primary purpose of drinking, are related to increased drinking. A greater presence of network drinking buddies is associated with increased individual drinking (Lau-Barraco et al, 2012; Lau-Barraco & Linden, 2014; Leonard et al, 2000; Leonard & Homish, 2008; Neighbors et al, 2019). The influence of drinking buddies remains, even after considering the impact of general or heavy drinking by peers, which lends support to the unique influence of drinking buddies in the peer use relationship (Leonard & Homish, 2008; Reifman et al, 2006).…”
Section: Social Network and Alcohol Usementioning
confidence: 99%